Socio-economic implications and potential structural adaptations of the Tunisian agricultural sector to climate change - Frija, Aymen; Oulmane, Amine; Chebil, Ali; Makhlouf, Mariem (MDPI, 2021)
Climate change is expected to have serious economic and social impacts on Tunisian rural farmers. The extent of these impacts will largely depend on the level of political and structural adaptations. This study aims to evaluate the effect of increasing water shortages on agricultural income and employment. It also analyzes structural adaptation strategies implemented by farmers in response to this challenge. We have therefore developed a regionally disaggregated supply model to simulate three types of scenarios concerning (i) decreasing quantities of irrigation water at the regional level; (ii) enhanced irrigation water use efficiency; and (iii) higher production prices. Observed crop production data for 21 crops and 24 districts of Tunisia have been used. Districts have been aggregated into five regions based on bioclimatic homogeneity. Results show that climate change will lead to the reduction of irrigated areas and an increased importance of rainfed agriculture. It will also have a negative impact on farm income and employment. This negative effect can be fully mitigated by improving water use efficiency, at farm and perimeter levels, and can be reversed by offering more attractive producer prices to farmers through enhanced value chain integration.